Letter from the Editor - Vargas, Carlos (Earth Sciences Research Journal, 2012)
Greatly appreciated readers of ESRJ,I am pleased to bring you Vol. 16(2) 2012 which contains interesting articles related to applying methods regarding seismic prospecting, geotechnics, geomorphology, seismology and geochemistry insuch varied countries as Japan, Turkey, Iran, Nigeria and Cameroon. Procedures for suitably treating seismic signals by using discrete wavelet transform (DWT), or treating clays aimed at modifying theirphysical attributes form part of the basic contributions regarding seismic engineering and geotechnics' immense usefulness......